Financial Regulation and the Current Account - Wieladek, Tomasz (IMF Working Papers; Working Paper ;, 2012)
This paper examines the relationship between financial regulation and the current account in an intertemporal model of the current account where financial regulation affects the current account through liquidity constraints. Greater liquidity constraints decrease the size and persistence of the current account response to a net output shock. The theory is tested with an interacted panel VAR model where the coefficients are allowed to vary with the degree of financial regulation. The current account reaction to an output shock is 60% larger and substantially more persistent in a country with low financial regulation than in one with high financial regulation.